KREATIVITAS GURU PAI DALAM MEMBINA AKHLAK SISWA DI SMA N 1 TIGO NAGARI KABUPATEN PASAMAN - Roza Lina; Darul Ilmi; Jasmienti Jasmienti; Alimir Alimir (KOLONI, 2022)
This research is motivated by the phenomenon from the author's observations that the range of moral development carried out by PAI teachers to their students has not gone well, because there are still many of their students who have morals that are not in accordance with the teachings taught by their teachers, such as smoking during recess, playing cellphones. when studying, rarely do assignments, clothes are not neat, often late, likes to pull out and likes to bully his classmates. This study aims to describe the Creativity of Islamic Education Teachers in Fostering Student Morals at SMA N 1 Tigo Nagari, Pasaman Regency. The research method used is a qualitative research method. The subject of this research is 1 PAI teacher and curriculum representative at the school. The data collection techniques used are observation and interviews, the data analysis in this study is a descriptive analysis technique and the data validity technique is observation, increasing persistence, triangulation, when it comes back to research later the researcher uses supporting reference materials and hacks. The results of data analysis show that creative teachers can be seen from four aspects of creativity, namely fluency in thinking, flexibility, originality, and elaboration. The results of the research from the four aspects of creativity that teachers have about the creativity of PAI teachers in fostering the morals of students at SMA N 1 Tigo Nagari, Pasaman Regency, not all teachers have criteria for these four aspects due to the low knowledge about creativity possessed by teachers. Even so, teachers continue to try to create ideas so that they can develop students' morals well. For example, they hold extracurricular activities and involve their students, so that their talents and interests are channeled and the purpose of the extracurricular itself is to avoid delinquency.  Keywords: Creativity, PAI Teacher, Fostering Morals